Yotsuba&!. 13 - Azuma, Kiyohiko (Yen Press, 2016)
Yotsuba has gotten back from her camping trip and comes bearing souvenirs for Asagi--like a good stick, a pinecone, and rock. Then Yotsuba decides to teach Fuuka to bake with sand, because Fuuka's not very good at it. Finally, Yotsuba will decorate the house with Ena to prepare for Grandma's visit.